Training on Digital Product Branding for MSMEs - Irwan Moridu; Rini Hadiyati; Khas Sukma Mulya; Asmita Wulansari Dg. Liwang; Nurcahya Hartaty Posumah (BADAN PENERBIT STIEPARI PRESS, 2023)
The purpose of community service activities is to stimulate the target audience's potential and creativity by including them in the development of Generation Z's creative economy through digitalization in the social age 5.0. The creative economy, developed as a concept in the social period 5.0, is a mainstay of technology and creativity, ideas, and human resources (HR) knowledge base. Creative industries in the social era 5.0, according to government programs, can become a reality if resources are available to meet digital, human, local, global, and balanced factors. Education, training, and mentorship are some of the methods used in this activity. This community service is intended at a group of Initiation (Muhammadiyah Luwuk University's Business Incubator) students. Among the programs implemented are those that explore student potential as a business goal, MSME innovation materials, and then training and mentorship related to product branding that encourages digital technical assistance. The findings demonstrated that the level of absorption (utilisation) of innovative MSMEs in Gen Z was high enough that they could be manufactured under private labels, notably in startup student groups (Muhammadiyah Luwuk University Business Incubator). As a result, students can unleash their potential and innovation in the creative economy sector before the complete digital society 5.0 phase.